Assessment of Workstation Design for Safe Working Posture at Plug Assembly Line - Isa, Halim; Adi , Saptari; Seri Rahayu , Kamat; Wan Hasrulnizzam , Wan Mahmood (2007)
Workstation design plays an important role to ensure a worker performs the job in safe working posture and thus increase occupational health. A good workstation design will be safe to the worker, otherwise it contributes to unsafe working posture. This research is carried-out to obtain the workstation design that offers safe working posture to the worker in plug assembly line. In development of the workstation, three factors were investigated: working height (table height : 91 cm and 103 cm), working position (standing and sitting) as well as the use of tool(with jig and without jig). These factors are employed in the design of the workstation to determine which factor contributes significantly to the safe working posture. Two subjects were participated in the research, and the experiment was conducted in the laboratory environment. Ergonomics assessment tool,Rapid Upper Limbs Assessment (RULA) associated with CATIA software was applied to analyze the working posture. Among three factors studied, the results concluded that the working height was found as significant contributor to achieve safe working posture.